2013
DOI: 10.1155/2013/381630
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in PBL Height over the Korean Peninsula in the KMA Operational Regional Model

Abstract: Spatial and temporal variations in planetary boundary layer height (PBLH) over the Korean Peninsula and its surrounding oceans are investigated using a regional grid model operated at the Korea Meteorological Administration (KMA). Special attention is placed on daily maximum mixing height for evaluation against two radiosonde observation datasets. In order to construct a new high-resolution PBLH database with 3-hour time and 10 km spatial resolution, short-term integrations with the regional model are carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The previous study shows that the thickness of CBL ranges from 1 km to 2 km in humid area through certain point observation or boundary layer statistics [9][10][11], while in the dry areas with severe surface thermal activity, such as western Sahara, the Arabian Peninsula Desert, the Taklimakan Desert, and the Gobi Desert (in Mongolia and Northwest China), the CBL thickness can stretch over 4 km in daytime [12][13][14]. Over recent years, the study on ABL characteristics under special geographical conditions and extreme climates exceeded people's expectation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study shows that the thickness of CBL ranges from 1 km to 2 km in humid area through certain point observation or boundary layer statistics [9][10][11], while in the dry areas with severe surface thermal activity, such as western Sahara, the Arabian Peninsula Desert, the Taklimakan Desert, and the Gobi Desert (in Mongolia and Northwest China), the CBL thickness can stretch over 4 km in daytime [12][13][14]. Over recent years, the study on ABL characteristics under special geographical conditions and extreme climates exceeded people's expectation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Note that OA concentrations are lower than sulfate concentrations above 1000 m, but higher below 1000 m (and that the relative concentrations of nitrate and ammonium also transition at 1000 m). It suggests that the sources and/or processing of the particle populations differ above and below 1000 m, which may approximate the planetary boundary layer height (PBLH), while the PBLH can vary widely (previous research has shown average summer values of ~1000-1400 m over Seoul (Lee et al, 2013). It is likely that the particles above 1000 m altitude were derived from transport, which is generally associated with enhanced sulfate formation (see Fig.…”
Section: Flight Type 2: Vertical Profiles Of Aerosol Chemical Composition and Physical Propertiesmentioning
confidence: 98%
“…Various observations and numerical models are used to monitor air quality and meteorological factors that significantly affect human lives [4][5][6][7][8][9]. Among them, the PBL height (PBLH) plays a key role in ground air pollution because of the inversion layer directly above the PBL [6].…”
Section: Introductionmentioning
confidence: 99%
“…If vigorous convection occurs, the PBLH increases, whereas if there is little convection and the atmosphere is stable, the PBLH decreases. Lee et al [7] examined the horizontal distribution of the PBLH and the related spatiotemporal structures in the Korean Peninsula and surrounding seas in order to evaluate. The CO 2 dynamics Sustainability 2021, 13, 8954 2 of 13 and the dispersion of air pollutant for developing a model boundary layer scheme.…”
Section: Introductionmentioning
confidence: 99%